Effects of molybdenum on sperm quality and testis oxidative stress. (October 2013) - Zhai, Xiao-Wei; Zhang, Yu-Ling; Qi, Qiao; Bai, Yu; Chen, Xiao-Li; Jin, Li-Jun; Ma, Xue-Gang; Shu, Run-Zhe; Yang, Zi-Jun; Liu, Feng-Jun
<x xml:space="preserve">Abstract</x> In order to investigate the effects of molybdenum (Mo) on sperm parameters and testicular oxidative stress, the ICR strain of adult mice were exposed to different doses of molybdenum for a sub-acute toxicity test. Compared to the control, our results showed that the sperm parameters, including the epididymis index, sperm motility, sperm count, and morphology, increased by a moderate dose of Mo (25 mg/L), but were negatively affected at high doses (≥ 100 mg/L). In addition, the changes of sperm parameters were accompanied with changes of the superoxide dismutase (SOD) activities, the glutathione peroxidase (GPx) activities, and the malondialdehyde (MDA) levels in testes. In conclusion, Mo affects the sperm quality through regulating the testicular oxidative stress in a complex manner.